Efeitos de interações elétron-elétron e spin-órbita nas propriedades magneto-eletrônicas de magneto-transporte de sistemas confinados - Destefani, Carlos Fernando (2003)
Effects of the direct and exchange electron-electron interaction, external magnetic field, symmetry of the charge carriers confining potential, radius, material g-factor, and also of the spin-orbit interaction in zincblende structure materials, are treated on the electronic and transport properties of semiconductor quantum dots (islands) charged by many particles. Three distinct kinds of confining potentials are considered: spherical, parabolic, and quasi-one-dimensional which, respectively, define a three-dimensional, two-dimensional, and one-dimensional island; the first one is more appropriated for the description of quantum dots formed in glassy matrices, while the last two better describe quantum dots litographically defined in a two-dimensional electron gas. Transport properties are considered in the spherical and quasi-one-dimensional islands, where we assume that the electronic current is in the resonant tunneling ballistic and coherent regimes, with essential role played by the excited states of the specific symmetry. We show that different geometries induce distinct level ordering in the island and that there is, in addition to the usual spin blockade, another kind of blockade mechanism which influences the system current; we label it by orbital blockade, because it is essentially due to the structure geometric confinement. We calculate the electronic spectrum of the many-particle system according to its symmetry. In the spherical case, we firstly use the LS-coupling scheme in order to obtain the eigenstates of an island charged by 3 electrons, following the orbital L and spin S total angular momentum addiction rules; we consider intensities of the magnetic field that allow us to neglect its diamagnetic contribution; the electron-electron interaction is treated as a perturbation in a Hartree-Fock way. In the following we use, in this same symmetry, the Roothaan and Pople-Nesbet matrix methods in order to deal with islands charged by 40 electrons, where the addition spectrum is calculated and Hund s rule is verified; we show how a magnetic field is able to violate such rule. The advantage of this numerical approach is the possibility to deal with a very high occupation in the island; the disadvantage is that their eigenstates do not have defined L and S values, as it is the case in the LS-coupling scheme. In the parabolic case, we employ a numerical diagonalization in order to obtain the island eigenstates charged by 2 electrons, without any restrictions regarding the magnetic field intensity or the system radius; we take into account both possible spinorbit couplings, one related to the implicit absence of zincblende crystalline structure inversion symmetry (Dresselhaus effect), and the other one related to the absence of structure inversion symmetry as caused by the confinement defining the two-dimensional electron gas (Rashba effect); we analyze the critical magnetic fields where both effects give origin to a intrinsic spin mixture in the island, inducing level anticrossings in the Fock-Darwin spectrum where intense spin-flips processes occur. In the quasi-onedimensional case, we just reproduce a known spectrum for an island charged by 4 electrons.